"But there are no snakes in the wood": risk mapping as an outcome measure in evaluating complex interventions. Issue 3 (7th March 2007) - Power, Robert; Langhaug, Lisa; Cowan, Frances
Abstract : Objectives: To complement biological and social behavioural markers in evaluating the complex intervention of sexual and reproductive health among adolescents in rural Zimbabwe, community-derived markers of effectiveness were sought. Through a participatory workshop with adolescent boys and girls, an innovative "risk map research workshop" was developed to be conducted throughout the study sites. Methods: 78 gender-specific standardised workshops were conducted among secondary school students. Participants drew risk maps of their community. Focus group discussions explored each risk area identified on the map. Grounded Theory was used to create "categories" and "subcategories." Workshops continued to be held until "saturation", whereby no new categories emerged. "Axial coding" identified the inter-relationship between categories and subcategories according to their relevance to sexual and reproductive health risk. Results: Six "risk area" Grounded Theory categories emerged from the data: bush/rural terrain, commercial centres, homes, school environs, religious and spiritual venues, and roadsides. 17 subcategories emerged, grouped under each of the risk area categories, such as riverbeds, growth points, homesteads, classrooms, all-night prayer meetings and truck stops. Risks and the consequences of risks included sexually transmitted infections (including HIV), violence, sexual abuse, expulsion from school and illegal abortion. Conclusions: Risk maps provide unique data that can be used to measure more subtle changes that occur as a result of social behavioural interventions aimed at addressing reproductive and sexual health. Another round of risk map research workshops will be held towards the end of the study to explore changes in milieu, behaviour and experiences, and will complement and triangulate the biological and other social behavioural outcome measures.